Rhetorical art of the Deuteronomist: lampooning Solomon in First Kings - Newing, Edward G. (1994)
This study argues that a traditional, positive view of Solomon found in 1 Kings 3-5 has been systematically undermined and contradicted by the ancient editor of this piece of literature. To this effect, various rhetorical devices such as contradiction, repitition and dislocation were used by the ancient editor.
Keywords: 1 Kings 3-5; Ancient editor of literature; Contradictory traditions; Literary structure; Rhetorical techniques; Solomon's wisdom; Use of prayers